2021
DOI: 10.1038/s41598-021-87681-2
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput enrichment and isolation of megakaryocyte progenitor cells from the mouse bone marrow

Abstract: Megakaryocytes are a rare population of cells that develop in the bone marrow and function to produce platelets that circulate throughout the body and form clots to stop or prevent bleeding. A major challenge in studying megakaryocyte development, and the diseases that arise from their dysfunction, is the identification, classification, and enrichment of megakaryocyte progenitor cells that are produced during hematopoiesis. Here, we present a high throughput strategy for identifying and isolating megakaryocyte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Bone marrow dissection was performed as previously described [ 20 ]. Briefly, mice were euthanized by CO 2 asphyxiation, followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow dissection was performed as previously described [ 20 ]. Briefly, mice were euthanized by CO 2 asphyxiation, followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…The use of imaging flow cytometry is another way to differentiate MKs from leukocyte–platelet aggregates ( 114 ). It also adds morphological information using the shape, density, texture, and coincidence of fluorescence to discriminate different MK maturation steps ( 115 ). Morphology is an important parameter of MKs that can be obtained by immunohistology or immunofluorescence.…”
Section: Mk Identity and Methodology Advices For Further Studiesmentioning
confidence: 99%
“…Immunohistochemistry analysis of major thrombopoiesis organs (bone marrow and spleen) in mice revealed that PALLD deficiency had no effect on the number of megakaryocytes (Figure 3A-B). 28,29 CFU-MK assay indicated that PALLD deficiency did not impact the ability of bone marrow and fetal liver-derived cells to form colonies (Figure 3C). 30 The plasma TPO remained at a similar level in PALLD f/f and PALLD -/mice (Figure 3D).…”
Section: Palld Deficiency Impaired Megakaryocyte Differentiationmentioning
confidence: 99%